Privacy models for protecting personal medical information: a preliminary study - Samsuri, Suhaila; Ismail, Zuraini; Ahmad, Rabiah (IEEE Xplore Digital Library, 2011)
Information privacy is regarded as the most important subject matter, especially in a paperless-based environment for hospitals which have adopted the Hospital Information System (HIS). A comprehensive model on securing the information privacy is therefore needed as a guideline for internal system designers and developers in order to ensure the efficiency and the effectiveness of the system. Several useful models were suggested from previous studies but still need to be evaluated by relevant experts. This paper proposes a set of model which focuses in protecting personal medical information stored in an electronic medical record system. A preliminary study has been conducted by interviewing selective experts in related field. Hence, the findings shall enlist several useful models that are necessary for the development of a personal medical information system that is capable in preserving individual’s privacy.